Application of Augmented Reality for Gypsum Marketing Using Vuforia, Sketchup and Unity 3D - Ifaldi Danang Septiawan; Cindy Taurusta (Universitas Muhammadiyah Sidoarjo, 2021)
The development of technology and information is currently progressing very rapidly, marked by advances in the field of information and technology. One of the most popular technologies today is gadgets. This is revealed by research conducted by Strategy Analytics. The author took the initiative to create an android-based augmented reality technology that is useful for marketing a gypsum product. The method used by researchers is quantitative. The results that have been achieved from this research are adding insight into the latest technology and promotional media.